Les langues en débat dans une Europe en projet - Sokolovska, Zorana (Langages, 2021)
In recent decades, discourse promoting and valuing plurilingualism has permeated different spheres of society. It is shaped by various social players, among which the Council of Europe plays a central role in the production and circulation of discourse and ideas on plurilingualism in Europe. Materialised in various instruments, such as recommendations, guides and frames of reference, these ideas build the foundations of a discourse of authority. At the crossroads of sociolinguistics, discourse analysis and institutional anthropology, this book studies the emergence and circulation of ideas on languages within the Council of Europe through the examination of institutional texts produced between 1949 and 2008. In particular, it examines what plurilingualism is, its role and its implications for the management of Europe. It also proposes a critical reflection on the mobilisation and promotion of a certain vision of languages and plurilingualism in order to exercise power on the international scene. This book is aimed at sociolinguists, discourse analysts and anthropologists and will also be of interest to students and professionals in the politico-educational field. Zorana Sokolovska is a lecturer in sociolinguistics at the University of Fribourg and a lecturer in French linguistics at the Lucerne University of Teacher Education. Her research focuses on the role of institutions in the management of languages and their teaching-learning.